Acquired partial lipodystrophy and C3 glomerulopathy: Dysregulation of the complement system as a common mechanism - Fernando Corvillo; Margarita López-Trascasa (Nefrología (English Edition), 2018)
The activation of the alternative pathway of the complement is involved in the development of several renal diseases, such as atypical haemolytic uraemic syndrome and C3 glomerulopathy. In C3 glomerulopathy, a high percentage of patients have circulating levels of the autoantibody called C3NeF, which causes systemic dysregulation of the complement system. In some cases, the presence of this antibody has been related with abnormalities of adipose tissue, causing acquired partial lipodystrophy (Barraquer–Simons syndrome). Acquired partial lipodystrophy is an extremely rare disorder affecting the distribution of subcutaneous adipose tissue and that mainly onsets during childhood. These patients, in addition to possibly presenting with all the metabolic disorders associated with the adipose tissue defect, present with C3 hypocomplementemia and C3NeF and 25% have developed C3 glomerulopathy. Although it has been known for some time how the dysregulation of the complement system affects the kidneys, it remains unknown how it exactly affects adipose tissue; nevertheless, the relationship is quite clear. In this paper, we describe the connection between the complement system with the biology of the adipose tissue and its pathogenesis reflected from acquired partial lipodystrophy. Resumen: La activación de la vía alternativa del complemento interviene en el desarrollo de varias enfermedades renales, como el síndrome hemolítico urémico atípico o la glomerulopatía C3. En esta última enfermedad un elevado porcentaje de los pacientes presentan niveles circulantes de un autoanticuerpo denominado C3NeF, causante de la desregulación del complemento a nivel sistémico. En ciertos casos, la presencia de este anticuerpo se asocia con alteraciones en el tejido adiposo, causando lipodistrofia parcial adquirida (síndrome de Barraquer-Simons), una enfermedad ultra-rara que afecta a la distribución del tejido adiposo subcutáneo y que comienza principalmente durante la infancia. Estos pacientes, además de poder presentar los problemas metabólicos asociados al defecto en el tejido adiposo, presentan hipocomplementemia C3 junto con la presencia de C3NeF y, en un 25% de los casos desarrollan una glomerulopatía C3. Aunque se sabe desde hace tiempo cómo la desregulación del sistema del complemento afecta al riñón, se desconoce de forma precisa cómo lo hace en el tejido adiposo; no obstante, su relación está bastante clara. En este artículo se va a describir la relación del sistema del complemento con la biología del tejido adiposo y su patogenia reflejada a partir de la lipodistrofia parcial adquirida. Keywords: Complement, Acquired partial lipodystrophy, C3 glomerulopathy, C3NeF, Palabras clave: Complemento, Lipodistrofia parcial adquirida, Glomerulopatía C3, C3NeF